(untitled) (Journal of Computational Mathematics, 1993)
This paper provides a new method for approximating matrix-valued functions — square Padé approximation. Some computational methods of the approximants are given. For accelerating matrix sequences, a family of nonlinear extrapolation formulas based on the square Padé approximation is given, a convergence acceleration theorem is proved and numerical examples are presented.